Micro-Scale Distribution of CA4+ in Ex vivo Human Articular Cartilage Detected with Contrast-Enhanced Micro-Computed Tomography Imaging - Karhula, Sakari S.; Finnilä, Mikko A.; Freedman, Jonathan D.; Kauppinen, Sami; Valkealahti, Maarit; Lehenkari, Petri; Pritzker, Kenneth P. H.; Nieminen, Heikki J.; Snyder, Brian D.; Grinstaff, Mark W.; Saarakkala, Simo (Frontiers in Physics, 2017)
Contrast-enhanced micro-computed tomography (CEµCT) with cationic and anionic contrast agents reveals glycosaminoglycan (GAG) content and distribution in articular cartilage (AC). The advantage of using cationic stains (e.g. CA4+) compared to anionic stains (e.g. Hexabrix®), is that it distributes proportionally with GAGs, while anionic stain distribution in AC is inversely proportional to the GAG content. To date, studies using cationic stains have been conducted with sufficient resolution to study its distributions on the macro-scale, but with insufficient resolution to study its distributions on the micro-scale. Therefore, it is not known whether the cationic contrast agents accumulate in extra/pericellular matrix and if they interact with chondrocytes. The insufficient resolution has also prevented to answer the question whether CA4+ accumulation in chondrons could lead to an erroneous quantification of GAG distribution with low-resolution µCT setups. In this study, we use high-resolution µCT to investigate whether CA4+ accumulates in chondrocytes, and further, to determine whether it affects the low-resolution ex vivo µCT studies of CA4+ stained human AC with varying degree of osteoarthritis. Human osteochondral samples were immersed in three different concentrations of CA4+ (3 mgI/ml, 6mgI/ml, and 24 mgI/ml) and imaged with high-resolution µCT at several timepoints. Different uptake diffusion profiles of CA4+ were observed between the segmented chondrons and the rest of the tissue. While the X-ray -detected CA4+ concentration in chondrons was greater than in the rest of the AC, its contribution to the uptake into the whole tissue was negligible and in line with macro-scale GAG content detected from histology. The efficient uptake of CA4+ into chondrons and surrounding territorial matrix can be explained by the micro-scale distribution of GAG content. CA4+ uptake in chondrons occurred regardless of the progression stage of osteoarthritis in the samples and the relative difference between the interterritorial matrix and segmented chondron area was less than 4%. To conclude, our results suggest that GAG quantification with CEµCT is not affected by the chondron uptake of CA4+. This further confirms the use of CA4+ for macro-scale assessment of GAG throughout the AC, and highlight the capability of studying chondron properties in 3D at the micro scale.